Implementation of a Web-Based Digital E-Catalog System Conceptual Design to Support Creative Entrepreneurship: A Case Study of Diorama Handmade Studio - Maullana, Chandra; Soeryanto Soegoto, Eddy; Wahdiniwaty, Rahma; Sumitra, Irfan Dwiguna; Mukharil Bachtiar, Adam (International Journal of Research and Applied Technology (INJURATECH), 2025)
The development of MSMEs in the era of digital transformation requires a product communication model that is not only informative but also capable of integrating visual identity, system architecture, and creative entrepreneurship strategies in an integrated manner. This study aims to design and implement a conceptual design for a web- based digital E-Catalog system at Diorama Handmade Studio that functions not only as an information medium but also as a strategic instrument for strengthening visual identity and developing creative entrepreneurship. The method used is a case study with a qualitative approach through observation, in-depth interviews with brand owners, system documentation, and literature studies related to digital information media, UI/UX, and creative entrepreneurship. The system was developed using a Responsive Web Application (RWA) approach with a three-tier architecture (presentation layer, application layer, and data layer) and implemented at the Proof of Concept (PoC) stage. The results of the study show that the digitally designed E-Catalog is capable of representing the complexity of handmade product values through interactive zoom features, organized information structures, brand storytelling, and a dynamic database-based filtering system.